2008
DOI: 10.1001/archpedi.162.8.748
|View full text |Cite
|
Sign up to set email alerts
|

Community Supports After Surviving Extremely Low-Birth-Weight, Extremely Preterm Birth

Abstract: Objective To determine special outpatient services (SOS) use, need, associated factors, and neurodevelopmental and functional outcomes among extremely preterm infants at 18 to 22 months’ corrected age. Design Retrospective analysis. Setting National Institute of Child Health and Human Development (NICHD) Neonatal Research Network. Participants Infants younger than 28 weeks’ gestational age who had been born weighing less than 1000 g at an NICHD Neonatal Research Network center from January 1, 1997, to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…In addition to higher rates of morbidity than fullterm infants, VLBW/ELBW preterm infants experience an increased incidence of hospital readmission, especially during the first 2 years of life, which is more than twice that reported for preterm children without BPD [21][22][23][24][25]. These children also have greater need for outpatient services in early childhood [26]. These issues are (Table 3) [27][28][29][30][31].…”
Section: Discharge Planningmentioning
confidence: 99%
“…In addition to higher rates of morbidity than fullterm infants, VLBW/ELBW preterm infants experience an increased incidence of hospital readmission, especially during the first 2 years of life, which is more than twice that reported for preterm children without BPD [21][22][23][24][25]. These children also have greater need for outpatient services in early childhood [26]. These issues are (Table 3) [27][28][29][30][31].…”
Section: Discharge Planningmentioning
confidence: 99%
“…It is important to note that even those risk factors, although not lethal, have been associated with adverse outcomes in later life. For example, low birth weight and very low birth weight increase risks of many neurodevelopmental and functional deficits [23,24].…”
Section: Negative Consequences Of Prenatal Cocaine Usementioning
confidence: 99%
“…Even in the highest risk neonates, access to community and early intervention supports was problematic and fragmented at best (>40% not enrolled in early intervention). Those toddlers with higher rates of disability were more likely to receive more services, yet a significant unmet need for services was documented among milder cases (Hintz et al 2008). Second, a Chicago-based cohort was followed after NICU discharge and demonstrated that less than 60% of VLBW infants living in extreme poverty (<50% federal poverty level) were receiving early intervention (EI) services despite having access to a medical home and legal advocacy.…”
Section: Postnatal and Social Riskmentioning
confidence: 99%